Analysis of scientometric indicators of Kazakhstani authors’ publication activity in journals, included in the Scopus database - Смагулов, К.; Маканова A.; Буршукова, Г. (Journal of Economic Research & Business Administration, 2018)
This article describes methods and findings of the research dedicated to investigation of publication activity of Kazakhstani authors for the period from 2009 to 2017. This time period was chosen based on the laws and regulations in the field of science of the Republic of Kazakhstan, adopted in 2011. Those regulations contributed to the quantitative growth of publications made by Kazakhstani authors in the largest international abstract and citation database of peer-reviewed literature Scopus. The analysis performed on the basis of selected methods has shown that starting from 2011 the number of publications by Kazakhstani authors among the editions enlisted in Scopus database has been gradually increasing. On the basis of this analysis the authors proved the hypothesis that the numerical growth of publications by Kazakhstani authors in Scopus editions has been stipulated by a rapid increase of works published in «predatory» journals and magazines – fact, which consequently associates with researchers of social and humanities studies striving to get academic titles. This paper provides comprehensive analysis of dynamics of the number of works published in «predatory» journals, types of facilitating agencies, which provide services for scientific publications in journals listed in international databases, and the most well-known types of «predatory» journals and magazines. Based on the analysis findings of publication activity of Kazakhstani authors in Scopus editions, the authors provide recommendations for quality improvement of national scientific publishing and struggle against unfair publishing houses.